Effects of nutritional plans and genetic groups on quantitative traits of pigs - Veloso, Rogério de Carvalho (2016)
Selection of genotypes for high performance led to a fat level reduction and loss of meat quality as consequence. An alternative to improve meat quality is the crossbreeding of non-selected local pig breed, such as Piau, with improved breeds such as Duroc, Pietrain and Large White. However, growth rate and fat deposition differences in pigs indicate that genetic groups have different nutritional needs. Genetic and environment are important in expression of performance and meat quality traits, mainly when variations in deposition of lean and fat tissue rates are observed. These variations may affect genes expression profile that acts in metabolic or hormonal pathways of meat quality related traits. In this work, we aimed to evaluate the effects of paternal genetic group (Piau, Duroc-based and Pietrain) and nutritional plans with different digestible lysine levels (Low, Medium and High) on performance, carcass and meat quality traits; gene expression pattern of myosin heavy chain isoforms (MyHC) in Longissimus and Psoas muscles; and differential expression of lipid metabolism-related genes (FAS, H-FABP, SCD, PRKAG1, PRKAG3 and HSL) in Longissimus muscle of pigs. Pietrain and Duroc crossbred barrows and gilts were similar in performance and carcass traits and had greatest values compared to Piau crossbred pigs. Regarding the meat quality, drip loss was greater in Pietrain crossbred barrows and gilts compared to Duroc and Piau crossbred pigs. Daily digestible lysine intake was greater in High nutritional plan animals in relation to Medium and Low nutritional plans. Most of performance, carcass and meat quality traits evaluated in barrows and gilts were not affected by nutritional plans. Expression levels of H-FABP and SCD were higher in Duroc and Pietrain pigs. Higher expression of PRKAG3 gene in barrows fed with Low nutritional plan compared with pigs fed with Medium and High nutritional plan was observed. There was a higher expression of MyHC IIb gene in Longissimus muscle of crossbred barrows fed with greater digestible lysine levels compared to crossbred barrows that received nutritional plan with lower digestible lysine levels. The mRNA expression levels of MyHC IIb in Longissimus muscle was higher in Duroc and Pietrain crossbred compared to Piau crossbred barrows (P < 0.05). In general, Duroc and Pietrain crossbred pigs had greater performance and carcass rate compared to Piau crossbred pigs. The present study indicated that genotype has a strong effect on intramuscular fat content deposition mainly by up-regulation of intramuscular lipogenic gene expression. The differentially expression of MyHC isoforms in muscles may be the most important factors affecting intramuscular fat content and drip loss in pig. These results may provide valuable information to the understanding of meat quality differences in divergent genetic groups of pigs.